Tonalidades afetivas e poesia: uma analogia possível no Heidegger da viragem - Brito, Marcos Antonio de Souza (2015)
The present research investigates two themes (parts of a single issue) connected to two distinct phases in Heidegger's thinking . In relation to the first phase (the so-called "first Heidegger"), the search is returned strongly to the shades affective (Stimmungen) according to that were addressed in Being and time, especially in §. 29, And fundamental concepts of metaphysics: world, finitude, solitude. Such affective tones were presented as ontological structures responsible for making sure that the being-there is always in a state of "willing to ... ". The provision, "be willing to ... " since any affective tone, form, along with understanding and discourse, the existential that portray how the being-there is in the world. The second phase (the so-called "second Heidegger") the theme ruled was the poetry, designed understood how language originated. The poetry was differentiated from poem by it should not be confused with mere literary style. The poetry while language originating in (Dichtung) brings the loved for the first time in the open air to nominate him, while poem (Poiesie) is identified with the art of making poems. Affective Tone and poetry were discussed from a point of view ontological. The transition to the second phase was worked from what became known as the "turning point" (Kehre). To deal with the change we have made it clear that there is no contradiction between the phases, there is seen that Heidegger, without denying the turning point, for more than once stated that his philosophy dealing with a single issue. The turning point became evident in the 1930s and marked a repositioning of the question raised in Being and time. The project of fundamental ontology, this in Being and time, was carried out from three sub-projects: existential analytical, destruction of the history of metaphysics and hermeneutics of facticity . The existential analytical, from which were analyzed the shades, fell on the being-there and has reached its limit by the impossibility of justifying historical ontologies, hence there was talk of "failure" in Being and time . Put the themes in evidence, was the work of an analogy, possible by taking into account the ontological characteristics regarding the affective tones and the poetry.